Analisis Keseuaian Lahan untuk Pengembangan Tanaman Kehutanan di Sub DAS Ake Leijemata DAS Ake Lamo Kabupaten Halmahera Barat - Sardin Sardin; Ramli Hadun; Suratman Sudjud (Jurnal Pertanian Khairun, 2022)
The pressure on land resources in the Ake Leijamata Sub-DAS is mainly related to increasing the use of land for agriculture. The increase in land use for agriculture in the Ake Leijemata Sub-DAS has led to the conversion of limited production forest (LPF) and Protected Forest (PF) areas to agricultural land. So that the condition of the Ake Leijamata Sub-DAS does not continue to experience a decline in quality, a land use plan that is in accordance with its potential is needed through land suitability analysis. This study aims to evaluate land suitability and determine land management directions for the development of teak and jabon crops in the Ake Leijamata Sub- DAS. This study used the purposive sampling method where the observation of homogeneous land units (12 units of land). Land suitability analysis uses a matching method between land quality and the requirements for growing crops including teak and jabon plants. The results showed that the actual land suitability for teak and jabon crops was 771.3 ha (48.9%) and non-conforming (N) covering an area of 806.9 ha (51.1%). In particular, the appropriate land is divided into sufficient classes (S2) covering an area of 399.3 ha (25.3%) and according to marginal (S3) covering an area of 372.0 ha (23.6%). In potential conditions, very suitable class land (S1) covering an area of 35.6 ha (2.3%), quite appropriate (S2) covering an area of 363.7 ha (23.0%) and marginalized (S3) covering an area of 372.0 ha (23.6%).Â  Efforts to improve dry month limiting factors through the provision of water from surface water (river water) or the manufacture of water harvesting buildings (dams), rainfall limiting factors specifically for teak plants are improved through soil treatment and the manufacture of drainage channels, nitrogen and potassium nutrient limiting factors are improved through the application of urea and KCl fertilizers or using compound fertilizers (phonska). Improvement of erosion hazard limiting factors through the application of agroforestry systems, planting according to contours, and planting of ground cover crops (legume cover croop). Meanwhile, improvements to the threat of flooding can be done through the creation of flood prevention buildings or planting plants on river embankments.